De novo variants in SIAH1, encoding an E3 ubiquitin ligase, are associated with developmental delay, hypotonia and dysmorphic features. Issue 3 (19th May 2020) - Buratti, Julien; Ji, Lei; Keren, Boris; Lee, Youngha; Booke, Stephanie; Erdin, Serkan; Kim, Soo Yeon; Palculict, Timothy Blake; Meiner, Vardiella; Chae, Jong Hee; Woods, Christopher Geoffrey; Tam, Allison; et al.
Abstract : Background: Ubiquitination has a central role in numerous biological processes, including cell development, stress responses and ageing. Perturbed ubiquitination has been implicated in human diseases ranging from cancer to neurodegenerative diseases. SIAH1 encodes a RING-type E3 ubiquitin ligase involved in protein ubiquitination. Among numerous other roles, SIAH1 regulates metabotropic glutamate receptor signalling and affects neural cell fate. Moreover, SIAH1 positively regulates Wnt signalling through ubiquitin-mediated degradation of Axin and accumulation of β-catenin. Methods: Trio exome sequencing followed by Sanger validation was undertaken in five individuals with syndromic developmental delay. Three-dimensional structural modelling was used to predict pathogenicity of affected residues. Wnt stimulatory activity was measured by luciferase reporter assays and Axin degradation assays in HEK293 cells transfected with wild-type and mutant SIAH1 expression plasmids. Results: We report five unrelated individuals with shared features of developmental delay, infantile hypotonia, dysmorphic features and laryngomalacia, in whom exome sequencing identified de novo monoallelic variants in SIAH1 . In silico protein modelling suggested alteration of conserved functional sites. In vitro experiments demonstrated loss of Wnt stimulatory activity with the SIAH1 mutants, suggesting variant pathogenicity. Conclusion: Our results lend support to SIAH1 as a candidate Mendelian disease gene for a recognisable syndrome, further strengthening the connection between SIAH1 and neurodevelopmental disorders. Furthermore, the results suggest that dysregulation of the Wnt/β-catenin pathway may be involved in the pathogenesis.